Dimensi Arsip Dalam Pembangunan Berkelanjutan di Kepulauan Riau: Warisan Budaya, Pembentuk Identitas, Tulang Punggung Manajemen, Penentu Arah Pembangunan - Shanti Oktaviana (Jurnal Archipelago, 2024)
The cultural heritage dimension is one of the indicators of cultural development that is in line with the context of sustainable development. Cultural heritage cannot be separated from the context of archives as a memory that builds a new paradigm about the other side of archives. Archives as a documentary heritage that strengthens the values of Malay culture and Islam as an advantage of the Riau Islands in sustainable development. Archives have information and historical value that are used in determining the direction and goals of the development of the Riau Islands while adhering to the values of Malay religion and culture. Cultural issues illustrate the suboptimal development of a culture-based economy in the Riau Islands, ranging from limited infrastructure, regulatory and policy schemes, lack of community participation, to limited accessibility and information resources in the management of archives of cultural historical value. The purpose of this research is to build insight into archives in various dimensions, where archives are documentary heritage as well as a source of information in strengthening culture as one of the important elements is sustainable development. This research is a descriptive qualitative research with a data collection method in the form of a literature study. The results of the study show that archives have various dimensions that play a role in sustainable development, ranging from the existence of archives as cultural heritage, shaping regional identity and image, the backbone of management, to determining the direction of development.